1979
DOI: 10.1111/j.1399-3054.1979.tb02610.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Forms of Nickel and Cobalt in Phloem of Ricinus communis

Abstract: Investigations were performed to study the chemical form in which nickel and cobalt are transported in sieve tubes. Ricinus communis plants were used since they allow easy collection of relatively pure phloem sap. In the experiments labelled nickel or cobalt were given to the nutrient solution. The tapped phloem exudate was separated by gel filtration on Sephadex or by paper electrophoresis. Nickel and cobalt were bound to complexing organic compounds with a molecular weight in the range of 1000—5000. The over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…NA is involved in the long distance transport of metals inside the xylem and phloem, but other chelators are required for loading. High molecular weight compounds that chelate Ni, Co, and Fe are found in the phloem of Ricinus communis plants (Wiersma and Van Goor 1979;Maas et al 1988) and Zn-chelating peptides are found in Citrus spp. (Taylor et al 1988) but they have yet to be characterized in detail.…”
Section: Root-to-shoot Metal Translocationmentioning
confidence: 99%
“…NA is involved in the long distance transport of metals inside the xylem and phloem, but other chelators are required for loading. High molecular weight compounds that chelate Ni, Co, and Fe are found in the phloem of Ricinus communis plants (Wiersma and Van Goor 1979;Maas et al 1988) and Zn-chelating peptides are found in Citrus spp. (Taylor et al 1988) but they have yet to be characterized in detail.…”
Section: Root-to-shoot Metal Translocationmentioning
confidence: 99%
“…Currently, little information is available concerning the chemical forms of Ni and Mn in the phloem sap. In R. communis , Mn has been detected in association with low molecular weight peptides (van Goor and Wiersma 1976), whereas Ni can be complexed with negatively charged organic compounds with a molecular weight in the range of 1,000–5,000 Da (Wiersma and van Goor 1979).…”
Section: Vascular Transport Of Microelement Mineralsmentioning
confidence: 99%
“…Other alterations in the metabolism of decline-stage trees include elevations of wood pH (Wutscher 1981) and the level of wood phenolics (Wiersma and Van Goor 1979) with increases in scion bark and leaf proline (Street and Peterson 1982). In addition, carbonic anhydrase and indoleacetic acid (IAA) oxidase, both Zn-requiring enzymes activities, decreased in declining trees (Bausher 1979;.…”
Section: Citrus Decline and Soil Propertiesmentioning
confidence: 99%